2005
DOI: 10.1007/s00540-004-0278-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fentanyl on emergence characteristics from anesthesia in adult cervical spine surgery: a comparison of fentanyl-based and sevoflurane-based anesthesia

Abstract: The quality of emergence from anesthesia in patients with cervical spine surgery is improved with fentanyl-based anesthesia, but there is no difference between the use of propofol TCI and less than 1% sevoflurane as a concomitant sedative agent with fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…After a review of the titles and abstracts, 81 studies were selected and assessed for potential inclusion into this systematic review. After reading the full-text articles, 33 RCTs (published between 1994 and 2021) including 2209 participants were finally included ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No unpublished trials were identified with our eligibility criteria in the clinicaltrial.gov register.…”
Section: Resultsmentioning
confidence: 99%
“…After a review of the titles and abstracts, 81 studies were selected and assessed for potential inclusion into this systematic review. After reading the full-text articles, 33 RCTs (published between 1994 and 2021) including 2209 participants were finally included ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No unpublished trials were identified with our eligibility criteria in the clinicaltrial.gov register.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the trial characteristics. Fourteen trials investigated remifentanil as an intra-operative opioid regimen [25, 26, 28, 31, 32, 34-36, 38-41, 44, 47], five explored fentanyl [27,29,43,45,46], one alfentanil [33] and one sufentanil [37]; one trial compared fentanyl and alfentanil to a control group [30], and another, remifentanil, alfentanil and morphine to a control group [42]. All included trials administered volatile anaesthetics to maintain anaesthesia except five that administered propofol [27,30,31,36,39].…”
Section: This Investigation Was Conducted Following the 'Preferredmentioning
confidence: 99%
“…All included trials administered volatile anaesthetics to maintain anaesthesia except five that administered propofol [27,30,31,36,39]. Regarding the types of surgery, authors included patients scheduled for gynaecological surgery in eight trials [25-27, 31, 33, 37, 44, 45]; patients undergoing abdominal surgery in six trials [28,35,36,38,41,42]; and finally, we combined the remaining nine trials together into an 'other surgery' group [29,30,32,34,39,40,43,46,47].…”
Section: This Investigation Was Conducted Following the 'Preferredmentioning
confidence: 99%
“…It was shown that the quality of emergence from anesthesia in patients with cervical spine surgery was improved with fentanyl-based anesthesia, with no difference between the use of propofol TCI and sevoflurane as a concomitant sedative agent with fentanyl [22]. Magni et al [23] stated that there were no differences in terms of emergence time and recovery of early cognitive function between sevoflurane-fentanyl and propofol-remifentanil-based anesthesia in patients undergoing craniotomy.…”
Section: Discussionmentioning
confidence: 98%